Pengendalian Persediaan Sparepart Sepeda Motor dengan Menggunakan Material Requirement Planning di CV. Parna Jaya Motor Indrapura - Zaharuddin Zaharuddin; Abdul Azis Syarif; Denny Walady Utama; Dimas Pramana Putra; Alfi Dwanda Putra Mulia (Jurnal Simetri Rekayasa, 2022)
Inventory control is a company policy related to investment and service to consumers. CV. Parna Jaya Motor is a company engaged in the sale and repair of motorcycles. The problems that occur in this company are related to inventory controlspare partsthat causes consumer demand to bespare partsnot fulfilled. To overcome this, the company must be able to control inventoryspare partsso that consumer demand is fulfilled by applying the ABC Analysis method, then calculating the MRP to find out the number of orders (EOQ), order frequency (SS) and when to place an order again (ROP). The results of data processing using the method above obtained results for the ABC classification of 45 speciesspare parts,gotspare partsbelonging to class A consists of 13 speciesspare partswith an investment value of IDR 807,455,000 or 68% of the total investment, class B consists of 12 typesspare partswith an investment value of IDR 250,323,000 or 21% of the total investment and class C consisting of 20 typesspare partswith an investment value of IDR 127,266,000 or 11% of the total investment. Of 13 typesspare partsclass A which is a priority, EOQ results range from 28-293 units, F results range from 7-13 times/year, SS results range from 23-82 units, ROP results range from 95-303 units, and TC results everyspare partsranges from IDR 595,500 – IDR 1,075,200 with all TCspare partsRp. 10,101,900.